KAJIAN EMPIRIS TENTANG NIAT WHISTLEBLOWING PEGAWAI PAJAK - Ana Sofia; Nurul Herawati; Rahmat Zuhdi (Master of Accounting Universitas Trunojoyo Madura, 2013)
The aims of this research is to examine and analyze the effect of socialization and the Professional Commitment to whistleblowing intentions. The population in this research is tax official in tax service office of Pratama (Kantor Pelayanan Pajak Pratama) of North Gresik of 67 respondents. The questionnaires in this research were distributed to tax official with census. Data analysis used the multiple linear regression. The result of this reseach show that: 1) the socialization influence on whistleblowing intentions; 2) the professional Commitment has influence on whistleblowing intentions.